2015
DOI: 10.4038/ouslj.v9i0.7324
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antimicrobial Activity of Artocarpus heterophyllus and Artocarpus altilis Leaf and Stem Bark Extracts

Abstract: Increasing drug resistance of pathogens and negative consequences of antibiotic usage has led to the search for alternative medicines from nature. Many plants have been exploited to cure infectious diseases from time immemorial. The present investigation evaluated the antimicrobial and phytochemical properties of Artocarpus heterophyllus i.e. Jack fruit (Kos in Sinhala) and Artocarpus altilis i.e. Bread fruit (Dhel in Sinhala) leaf and stem bark extracts. Hexane, dichloromethane and ethanol were used as extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
5
9
0
Order By: Relevance
“…The authors also showed that P. aeruginosa and E. coli had lower zones of inhibition. The present study findings were in line with study conducted by Sivagnanasundaram and Karunanayake [ 48 ] which revealed that E. coli was resistant to leaf extracts of Artocarpus heterophyllus . The resistance of Gram-negative bacteria used in this study could be due to the extract's inability to penetrate the bacterial outer membrane.…”
Section: Discussionsupporting
confidence: 93%
“…The authors also showed that P. aeruginosa and E. coli had lower zones of inhibition. The present study findings were in line with study conducted by Sivagnanasundaram and Karunanayake [ 48 ] which revealed that E. coli was resistant to leaf extracts of Artocarpus heterophyllus . The resistance of Gram-negative bacteria used in this study could be due to the extract's inability to penetrate the bacterial outer membrane.…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirm those obtained by Prakash et al [29] and Sivagnanasundaram and Karunanayake [32] who also reported the presence of terpenoids in the leaves of A. heterophyllus.…”
Section: Phytochemical Screeningsupporting
confidence: 93%
“…These results are consistent with those of Thapa et al [31] and those of Sivagnanasundaram and Karunanayake [32] showing the presence of coumarins and anthraquinones in the leaves of A. heterophyllus Lam, respectively.…”
Section: Phytochemical Screeningsupporting
confidence: 92%
“…The result was in agreement with previous study which reported the ability of A. heterophyllus to reduce the frequency of diarrhea 15 . The ability of Artocarpus altilis to reduce the onset of diarrhea, frequency of diarrhea and duration of diarrhea might be due to the presence of tannin as reported in previous phytochemical study 8 . Tannins are able to narrow the cells so that preventing the muscle secretion 9 .…”
Section: Castor Oil-induced Diarrheamentioning
confidence: 56%
“…Indonesian people known this plant by its edible fruit. Phytochemical study of A. altilis led to the identification of saponins, tannins, steroids, flavonoids and polyphenols 8 . Tannins are well known secondary metabolite to have anti-diarrheal activity by narrowing the cells so that preventing the muscle secretion 9 .…”
Section: Introductionmentioning
confidence: 99%